(untitled) - Dunlap, Richard A. (Belmont, CA., 2004)
This text is intended for a one-semester senior-level course in nuclear and particle physics for physics majors. The course can also be taught as an introductory course for graduate students who have not had a previous undergraduate course in the subject. Chapters are in sections on basic concepts and interactions between particles, nuclear properties and models, nuclear decays and reactions, and particle physics. The author is affiliated with Dalhousie University.
Keywords: Particles ( nuclear physics ),Nuclear physics